Effects of local and whole-body cryotherapy on hip pain and general activity in the course of coxarthrosis - Widłak Patrycja; Kaczmarek Sylwia; Klimkiewicz Paulina; Łopuszańska-Dawid Monika (Sciendo, 2023)
Study aim: The purpose of this study was to compare the effects of whole-body and local cryotherapy on pain and function of the osteoarthritic hip.